2014
DOI: 10.3174/ajnr.a3959
|View full text |Cite
|
Sign up to set email alerts
|

Midbrain-Hindbrain Involvement in Septo-Optic Dysplasia

Abstract: BACKGROUND AND PURPOSE:Midbrain-hindbrain involvement in septo-optic dysplasia has not been well described, despite reported mutations of genes regulating brain stem patterning. We aimed to describe midbrain-hindbrain involvement in patients with septo-optic dysplasia and to identify possible clinical-neuroimaging correlations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Usually, involvement of the visual pathways in septo-optic dysplasia carries a much poorer prognosis than does septo-optic dysplasia with associated endocrine dysfunction 19 . Moreover, visual deficits are normally the first presenting sign, whereas endocrine dysfunction may become apparent later on 20 . Of the eight cases with agenesis of the SP in our study, five had OC measurements within the normal range and long-term follow-up showed normal vision in four of these.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, involvement of the visual pathways in septo-optic dysplasia carries a much poorer prognosis than does septo-optic dysplasia with associated endocrine dysfunction 19 . Moreover, visual deficits are normally the first presenting sign, whereas endocrine dysfunction may become apparent later on 20 . Of the eight cases with agenesis of the SP in our study, five had OC measurements within the normal range and long-term follow-up showed normal vision in four of these.…”
Section: Discussionmentioning
confidence: 99%
“…In order to objectively evaluate associated MH malformations, the following biometric parameters were measured in all the MRI examinations of patients with DMJ anomalies as well as in controls: the craniocaudal (CC) and anteroposterior (AP) diameters of midbrain, pons, medulla, and vermis and the transverse cerebellar diameter [15]. All measurements were performed by two pediatric neuroradiologists (M.S.…”
Section: Midbrain-hindbrain Morphometrymentioning
confidence: 99%
“…Occasionally, cortical abnormalities (especially schizencephaly, polymicrogyria, and nodular gray matter heterotopias), hippocampal malrotation, and white matter hypoplasia with secondary thinning of the corpus callosum. Posterior fossa involvement including vermian, pontine, and lower brainstem hypoplasia in about 50% of the patients …”
Section: Glossarymentioning
confidence: 99%
“…Posterior fossa involvement including vermian, pontine, and lower brainstem hypoplasia in about 50% of the patients. 297 Genitopatellar syndrome (OMIM: 606170) General information: About 20 cases reported so far. Somatic findings: Extremity contractures, urogenital anomalies, developmental disability, and facial dysmorphic features including coarseness of the face, microcephaly, a large nose, and a high nasal bridge.…”
Section: Septo-optic Dysplasia (Omim: 182230)mentioning
confidence: 99%